Jane and Jerusha: Finding a voice on the musical stage. Issue 1 (1st March 2015) - Thornton, Annette
In 1994, American composer/lyricist Paul Gordon started to work with British stage director and writer John Caird on the musical Jane Eyre, which finally opened on Broadway in 2000 with Caird writing the book, additional lyrics and co-directing the production. The two artists again collaborated on Daddy Long Legs in 2008, also with book and direction by Caird. Both musicals feature a female protagonist and are adapted from novels written and set in earlier times – 1847 and 1912, respectively. In addition, the novels have been adapted to the screen with varying degrees of faithfulness to the source material. This article explores how screen adaptations have interpreted the two novels and compares these to the stage musicals. I argue that by being more faithful to the source material, Gordon and Caird make the characters and relationships modern, passionate, and relatable to twenty-first-century audiences.